Intraslab seismicity characteristics of northern ChileKey points - Zixin Chen; Lei Gao; Haijiang Zhang; Shaobo Yang; Ying Liu; Diana Comte (Earthquake Science)
The Chilean subduction zone is one of the most seismically active regions globally, characterized by extensive intermediate-depth seismicity in the slab. In this study, we construct a new earthquake catalog for northern Chile using seismic waveforms assembled for the period of 2014−2019, from which 320,070 P-wave and 232,907 S-wave first arrivals are obtained for 25,763 earthquakes. Grid search location method NonLinLoc is applied to determine initial earthquake locations and double-difference location method is used to improve relative event locations. The distribution of earthquakes exhibits distinct patterns to the north and south of 21°S. There are many more earthquakes deeper than ∼150 km to the south of 21°S, while relatively fewer to the north. The intraslab earthquakes shallower than ∼80 km generally reveal a distinct double seismic zone, and the gap between the two seismic planes disappears at a depth of approximately ∼80 km, followed by a concentration of seismicity in the depth range of ∼80−150 km. In the deeper slab, there exist several seismicity clusters with distinct earthquake activities down to ∼300 km. These characteristics shown in slab seismicity are likely caused by different mechanisms and can be helpful for understanding the subduction process.